2014
DOI: 10.5114/pr.2014.48907
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase polymorphisms as possible risk factors of venous thrombosis – too weak to take care, too frequent to be ignored…

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is an enzyme involved in the metabolism of homocysteine. It has been found that an increased concentration of homocysteine in circulating blood (hyperhomocysteinaemia) may lead to blood vessel damage, which may further be associated with higher risk of various cardiovascular disorders, including venous thrombosis (VT). Among various factors identified to be responsible for hyperhomocysteinaemia, an important role is played by the genetically determined decrease of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…This finding, since it is similar to other reports, was not surprising. However, that risk, although considerably low, was still statistically significant when including relatively mild and indirect risk factors -the polymorphism of MTHFR (C677T) [8,9,15,16]. Thus, including in our model all SNPs mentioned previously, we found that 37.5% of patients with recurrent DVT, but only 12.8% of population controls, carried two or more alleles associated with increased risk of venous thrombosis.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This finding, since it is similar to other reports, was not surprising. However, that risk, although considerably low, was still statistically significant when including relatively mild and indirect risk factors -the polymorphism of MTHFR (C677T) [8,9,15,16]. Thus, including in our model all SNPs mentioned previously, we found that 37.5% of patients with recurrent DVT, but only 12.8% of population controls, carried two or more alleles associated with increased risk of venous thrombosis.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast to them, recessive MTHFR 677 T allele is supposed to influence the risk of DVT indirectly, since its pro-thrombotic role is associated with hyperhomocysteinaemia and may be modified, e.g. by concomitant diseases or folate and vitamin B levels [15,22,23]. On the other hand, MTHFR 677T allele, since present in almost 50% of individuals of the general population [9,15], may slightly augment the influence of other pro-thrombotic factors, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations